Increasing of Blood Brain Barrier Permeability and the Association With Depression and Anxiety in Systemic Lupus Erythematosus Patients - Wang, Xiangyu; Ma, Lihua; Luo, Yuli; Yang, Yifan; Upreti, Bibhuti; Cheng, Yuqi; Cui, Ruomei; Liu, Shuang; Xu, Jian (Frontiers in Medicine, 2022)
Objective: To study changes in blood brain barrier (BBB) permeability in systemic lupus erythematosus (SLE) patients, and explore the association between the alterations in BBB permeability and depression/anxiety in SLE. Methods: Brain dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) images were collected from 42 SLE patients and 23 healthy controls (HCs). Based on the Patlak pharmacokinetic model, the Ktrans value of each voxel in the whole brain of each subject was calculated. BBB permeability indicator (the Ktrans value) between SLE patients and healthy control group was compared. Hamilton Depression Scale (HAMD) and Hamilton Anxiety Scale (HAMA) were used to assess the mental health of SLE patients. The difference in BBB permeability was compared on SLE patients with depression/anxiety, SLE patients without depression/anxiety and HCs by ANOVA analysis. Results: The Ktrans value of the right insular region of the SLE group was significantly higher than that of the healthy control group. And the Ktrans value of the right insular region in SLE patients with depression/anxiety was significantly increased compared with SLE patients without depression/anxiety and HCs. Conclusions: SLE patients have increased BBB permeability, mainly in the right insular area. The increased BBB permeability in the right insular region is associated with the depression/anxiety in SLE patients.